Compressive Response and Energy Absorption Characteristics of In Situ Grown CNT‐Reinforced Al Composite Foams. Issue 12 (26th July 2017) - Yang, Xudong; Yang, Kunming; Wang, Jiwei; Shi, Chunsheng; He, Chunnian; Li, Jiajun; Zhao, Naiqin
Abstract : Carbon nanotube (CNT) reinforced Al composite foams with different CNT contents are fabricated through an improved powder metallurgy approach by combining in‐situ chemical vapor deposition (CVD), short time ball‐milling, and space‐holder method. The CNTs are uniformly dispersed on the surface of Al particles by in‐situ CVD process, followed by a short time ball‐milling process enabling an excellent interfacial bonding between CNTs and the Al matrix. The pore size and microstructures of the composite foams can be well tailored by the carbamide particle templates. The yield strength and energy absorption capacity of composite foams reach 18.1 MPa and 15.8 MJ m −3 with 3.0 wt% CNT addition, which are ≈1.3 and ≈3.6 times higher than those of pure Al foam, respectively. The energy absorption efficiency of the CNT/Al composite foams achieves a maximum of ≈0.86, when the CNT content is up to 3.0 wt%. Additionally, compressive and energy absorption properties of the CNT/Al composite foams increase with the increment of relative density. The failure mode of the Al foam changes from plastic mode to brittle mode combined with ductile mode, as a result of CNT addition. Abstract : Uniformly dispersed CNTs reinforced Al composite foams are successfully fabricated by the combination of an in situ chemical vapor deposition, short‐time ball‐milling, and space‐holder method. Besides, the pores well replicate the shape and size of the original spherical carbamide particles.